Children’s Perceptions of Professional Gender Stereotypes in the Finnish Early Childhood Education Classroom - Iskandar, Angeline (My University, 2024)
Attention towards gender stereotypes in educational setting has been increasing globally, including in Finnish early childhood education. The topics regarding the development of perceptions of gender stereotypes, factors that contribute to its development, gender stereotyped behaviors among young children, and also gender stereotyped behaviors and perceptions of early childhood education teachers have been discussed in previous studies. However, perceptions of gender stereotypes among children in Finnish early childhood education setting has not been widely explored. Literature has argued that associations between genders and professions develop during middle childhood, between six and nine years of age. This study aims to find out whether the perceptions of gender stereotypes have already existed among children in a Finnish early childhood classroom, specifically towards commonly gendered professions in Finnish society. Fourteen children aged four to six from one of the groups in a kindergarten in the Satakunta region were taken as the sample of this study. The data was collected by requesting the participants to draw predetermined professions and statistical analysis was applied to analyze the data. The findings indicated that children in early childhood already show gender stereotypes towards professions, regardless of their age and cultural backgrounds. The younger participants demonstrated perceptions of gender stereotypes as much as the older ones and there was no statistically significant difference in perceptions of gender stereotypes across different cultural backgrounds. Hence, this study concluded that perceptions of gender stereotypes towards professions has been established during early childhood and Finnish society still upholds gender stereotypes related to certain professions which was reflected through the children’s stereotypical perceptions. At the end of the study, theoretical and practical implications were suggested.
Keywords: gender stereotypes, professions, early childhood education, Finland